Exploring the Floral Marketing Practices: An Investigation of the Retail Floral Traders of Bangladesh - Ara, Husna; Hosen, Md. Mofazzal (Universiti Sains Malaysia, 2017)
The study of “Floral marketing” has become a catchphrase in both academic and practical arena, thus different issues related to floral marketing have been researched in many international studies. This study is designed on considering the contemporary trends of Floral Marketing in Bangladesh with the view of different Bangladeshi flower farmers and retail floral traders. For assessing the recent scenario, an exploratory research has been conducted. Investigations were carried out during the month of October 2016-January 2017 based on the group discussions and thorough case studies on the Bangladeshi florist business traders. The results reveal that the floral traders haven’t tailored these marketing concerns yet. Besides, it gives a rational perceptive to Bangladeshi traders of utilizing this floral marketing theory to bloom this industry by managing different complexities.